2010
DOI: 10.1103/physrevd.81.125016
|View full text |Cite
|
Sign up to set email alerts
|

Compactlike kinks and vortices in generalized models

Abstract: This work deals with the presence of topological defects in k-field models, where the dynamics is generalized to include higher order power in the kinetic term. We investigate kinks in (1,1) dimensions and vortices in (2,1) dimensions, focusing on some specific features of the solutions. In particular, we show how the kinks and vortices change to compactlike solutions, controlled by the parameter used to introduce the generalized models.Comment: 7 pages, 7 figures. Version to be published in PR

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 31 publications
3
94
0
Order By: Relevance
“…A postivie energy theorem for P (X, φ) theories coupled to Einstein gravity has been proved in [451,452]. Futher, P (X, φ) models have been supersymmetrized [453,454], and topological defects and solitons are studied in [455][456][457][458][459][460][461][462][463][464]. Analyses of screening in these models can be found in [197-200, 465, 466], along with studies of large-scale sctructure [467,468].…”
Section: Kinetic Screeningmentioning
confidence: 99%
“…A postivie energy theorem for P (X, φ) theories coupled to Einstein gravity has been proved in [451,452]. Futher, P (X, φ) models have been supersymmetrized [453,454], and topological defects and solitons are studied in [455][456][457][458][459][460][461][462][463][464]. Analyses of screening in these models can be found in [197-200, 465, 466], along with studies of large-scale sctructure [467,468].…”
Section: Kinetic Screeningmentioning
confidence: 99%
“…It is worth emphasizing the possibility that these theories can arise naturally within the context of string theory. Several studies concerning the topological structure of the -theories have shown that they also engender topological solitons [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]; in general, they can present some new characteristics when compared those of the usual ones [23].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of vortex solutions with compact-like profiles in -generalized Abelian Maxwell-Higgs model was studied in [50,51] and in -generalized Born-Infeld model [52]; however, only in [51] were the first-order vortices with compact-like profiles found. Therefore, the aim of this manuscript is to study the topological vortices engendered by the self-dual configurations obtained from the generalization of the following Abelian Higgs models: MaxwellHiggs (MH), Born-Infeld-Higgs (BIH), Chern-Simons-Higgs (CSH), and Maxwell-Chern-Simons-Higgs (MCSH).…”
Section: Introductionmentioning
confidence: 99%
“…For example one can introduce noncanonical kinetic terms [25][26][27][28][29][30][31][32], in order to circumvent the constraints of Derrick's theorem [33] and obtain topological defect solutions (see e.g. [34,35] for a more detailed account on soliton-like solutions in field theory).…”
Section: Introductionmentioning
confidence: 99%